Correction: Tai et al. Sea Bass Essence from Lates calcarifer Improves Exercise Performance and Anti-Fatigue in Mice. Metabolites 2022, 12, 531 - Hong-Jun Tai; Mon-Chien Lee; Yi-Ju Hsu; Chun-Yen Kuo; Chi-Chang Huang; Ming-Fu Wang (Metabolites)
First, in the original publication [...]